Exercise-induced cardiac dysfunction in sickle cell anemia. A radionuclide study - Covitz, W; Eubig, C; Balfour, I C; Jerath, R; Alpert, B S; Strong, W B; DuRant, R H (The American journal of cardiology, 1983)
Cardiac performance was studied by radionuclide angiography at rest and during exercise in 22 adolescents with sickle cell (SC) anemia and the results were compared with those in 12 control subjects. At rest, cardiac contractility was normal; cardiac output and end-diastolic volume were increased. At maximal exercise, heart rate, cardiac output response, and work capacity were reduced; the reduction was related to the degree of anemia. Left ventricular end-diastolic volume decreased with exercise most markedly in patients with ischemic exercise electrocardiograms. An abnormal ejection fraction response to exercise occurred in 4 patients; electrocardiographic signs of ischemia developed in all 4, and wall motion abnormalities in 2. Those patients who had electrocardiographic signs of ischemia had a significantly lower heart rate, ejection fraction, and cardiac output response to exercise, and a lower hematocrit level than subjects with normal results on exercise electrocardiography. The increase in cardiac output was not sufficient to maintain a normal level of exercise. The decrease in end-diastolic volume suggests that diastolic function was abnormal during exercise. Cardiac dysfunction was manifested by an abnormal ejection fraction response, wall motion abnormalities, and incomplete left ventricular filling during exercise.